CULTIVATING SUSTAINABLE PRACTICES: THE ROLE OF RENEWABLE ENERGY IN AGRICULTURAL EDUCATION - Thompson, Michael David (Ayden Journal of Agriculture and Allied Studies, 2024)
Agriculture is a substantial consumer of energy, encompassing not only fuel usage in food and fiber production but also in the manufacturing of critical inputs like pesticides and fertilizers. In 2012, the U.S. agricultural sector devoured an astounding 800 trillion British thermal units (Btu), mirroring the primary energy consumption of an entire state, Utah. Renewable energy sources contributed 12.2% to the nation's energy consumption, with renewable electricity generation comprising 14.94% of domestically produced electricity in 2016. An extensive study by the Department of Energy's National Renewable Energy Laboratory (NREL) even envisages the potential to derive 80% of U.S. electricity from renewable sources by 2050. This substantial energy consumption and the potential shift towards renewables prompts an essential question: Are consumers prepared for such a transformation in electricity generation sources? Public sentiment regarding new energy sources predominantly hinges on personal values, experiences, and the influence of trusted social networks. Notably, public opinion regarding energy issues overwhelmingly supports the expansion of both solar and wind power.